The reuse of treated sewage for agricultural purposes: a case study in Arapiraca (Northeast, Brazil) (Research, Society and Development, 2020)
Population growth and negative man-made environmental impacts on nature accelerate the reduction of water availability in certain regions. In this context, the reuse of treated sewage is a potential alternative, especially for agricultural activities. The municipality of Arapiraca, located in northeastern Brazil, stands out for its agricultural production, specifically in the Bananeiras pole, in its countrifields zone. Despite being inserted in a region of sub-humid tropical climate, the municipality has a picture of water scarcity. In this sense, the reuse of treated sewage may be a way of mitigating water scarcity and promoting agriculture in this locality. With the implementation of the municipality's basic sanitation system, this study aims to suggest a sustainable disposal for the planned Sewage Treatment Plant (STP). Thus, the potential for agricultural reuse of sewage treated at the STP was evaluated as a source of irrigation for farmers around that location, verifying compliance with the OMS, USEPA and PROSAB indexes. The obtained results were positive considering that the treated effluent, theoretically analyzed and based on the state of the art, depending on the efficiency level acquired during the treatment, met the analyzed parameters and the recommendations of the regulatory agencies that guide this theme.